Estabilização cervical em indivíduos com apneia obstrutiva do sono: ensaio clínico controlado randomizado - Turra, Patrícia (2017)
This study aims to evaluate the cervical flexor and extensor muscles strength, craniocervical posture, pain sensitivity to pressure and sleep quality, and to investigate the presence of craniocervical dysfunction (CCD) and temporomandibular dysfunction (TMD) in individuals with and without obstructive sleep apnea (OSA). The study also purposes to verify the effects of cervical stabilization in subjects with OSA on these variables. An observational (case-control) and an interventional (clinical trial) studies were performed. Men and women aged from 20 to 60 years old, with OSA diagnosis confirmed by polysomnography were invited to participate. The observational study sample consisted of 51 subjects, 26 in the AOS group (GAOS) and 25 in the non-OSA group (GsAOS). In the intervention study, the sample consisted of 22 patients with OSA, 11 in the treatment group (GT) and 11 in the control group (CG). At baseline, an anamnesis was carried out and participants answered the Epworth Sleepiness Scale (ESS), the Pittsburgh Sleep Quality Index (PSQI), and the STOP-Bang questionnaire, which identifies OSA risk. In addition, muscle strength was assessed by manual dynamometry, craniocervical posture by biophotogrammetry (SAPo v 0.68®), pain sensitivity by algometry, CCD by Craniocervical Dysfunction Score (CDS) and presence and severity of TMD, by the Diagnostic Criteria for Dysfunction Temporomandibular Index and Temporomandibular Index. In the interventional study, after the first evaluation, the GT participants underwent cervical stabilization treatment using pressure biofeedback (Stabilizer, Chattanooga, USA), with two weekly sessions and, after six weeks they were reassessed by the same questionnaires and instruments. GC was reassessed six weeks after initial assessment, when they underwent the same treatment. The main results found in the observational study were the lower values of cervical flexion range of motion (p <0.01), evaluated by the CDS, and pain threshold of the posterior mandibular region in GAOS (p <0.05), compared to GsAOS. Sleep quality presented moderate and significant correlation (r> 0.30, p <0.05) with TMD severity and with pain pressure threshold of temporal (middle and posterior region) and upper trapezius muscles. The interventional study showed that sleep quality, cervical flexor and extensor muscles strength, craniocervical posture, pain sensitivity and CCD did not differ between groups and between evaluations pre and post intervention (p> 0.05). The conclusion is that individuals with OSA had no difference in muscle strength, craniocervical posture and sleep quality, compared to GsAOS. OSA had repercussions on cervical dysfunction and mobility and craniocervical pain sensitivity. It was observed that the worse the quality of sleep, greater severity of TMD and greater pain sensitivity in the craniocervical region. Strength training of the deep cervical flexor muscles did not modify the variables related to sleep quality, muscle strength, craniocervical posture, pain sensitivity to pressure and CCD, which is attributed to their good condition before treatment and moderate degree of OSA.